Perancangan Prosthetic Hand Berbasis ESP32 dengan Sistem Kendali Nirkabel Real-Time untuk Penyandang Tunadaksa : ESP32-Based Prosthetic Hand Design with Real-Time Wireless Control System for the Physically Disabled - Sri Lestari; Permatasari, Indah; Fena Nur Mustika; Maulidya Fitria Zahrah; Irmayatul Hikmah (Lembaga Pengembangan Kinerja Dosen, 2026)
Individuals with physical disabilities, particularly those with impaired hand function, require assistive devices that can support daily activities independently. However, the development of prosthetic hands is often constrained by high costs, complex control systems, and limited accessibility of affordable technology. This study aims to design and implement an ESP32-based prosthetic hand with a real-time wireless control system that is simple, stable, and cost-effective. The proposed system employs an ESP32 and Arduino Uno as controllers, a hall effect linear sensor integrated in an electric bicycle throttle as the control input, and servo motors as finger actuators. System performance was evaluated through servo angle accuracy tests, object grasping and lifting experiments, and Quality of Service (QoS) analysis of wireless communication using Wireshark. Experimental results indicate that the system accurately follows commanded servo angles, successfully grasps objects with diameters ranging from 5.5 cm to 12 cm, and lifts loads up to 500 ml at heights between 10 cm and 50 cm. QoS evaluation conducted over 19,150 seconds shows a throughput of 1,737.59 kbps, an average delay of 4.572 ms, jitter of 4.571 ms, and zero packet loss, demonstrating fast and stable real-time communication. These results confirm that the developed prosthetic hand is responsive and functional, and has strong potential for further development as an affordable IoT-based assistive technology for individuals with physical disabilities.